선형계획법을 이용한 정수장 취수계획 최적화 - 정기문; 이인도; 강두선; Jeong, Gimoon; Lee, Indoe; Kang, Doosun (Journal of Korea Water Resources Association, 2019)
An optimization model of water intake planning is developed based on a linear programming (LP) for the intelligent water purification plant operation system. The proposed optimization model minimizes the water treatment costs of raw water purification by considering a time-delay of treatment process and hourly electricity tariff, which is subject to various operation constraints, such as water intake limit, storage tank capacity, and water demand forecasts. For demonstration, the developed model is applied to H water purification center. Here, we have tested three optimization strategies and the results are compared and analyzed in economic and safety aspects. The optimization model is expected to be used as a decision support tool for optimal water intake scheduling of domestic water purification centers. 본 연구에서는 지능형 정수장 운영시스템 개발 연구의 일환으로 선형계획법(Linear Programming, LP)을 이용한 정수장 취수계획 최적화 모형을 개발하였다. 개발된 최적화 모형은 원수의 정수처리비용의 최소화를 목적함수로 설정하였으며, 취수 후 정수처리에 소요되는 지연시간과 시간별 전력단가를 고려하여 취수가능량, 예측수요량, 정수지 운영수위 등의 제약조건을 만족하는 최적 취수계획을 제시하였다. 국내 H 정수장을 대상으로 경제적이고 안정적인 정수장 운영을 위해 세 가지 최적화 전략을 적용하고, 그 결과를 경제성과 안정성 측면에서 비교, 분석하였다. 개발 모형은 국내 정수장의 보다 효율적인 취수계획 수립을 위한 의사결정 지원시스템의 형태로 실무에서 활용이 가능할 것으로 기대된다.